Removal of hexavalent chromium from aqueous solution by different surface-modified biochars: Acid washing, nanoscale zero-valent iron and ferric iron loading. (August 2018) - Zhu, Yuen; Li, Hua; Zhang, Guixiang; Meng, Fanjian; Li, Lifen; Wu, Shan
Graphical abstract: Highlights: The Langmuir model well described adsorption isotherms for both raw and modified BCs. The reduction of Cr(VI) to Cr(III) was the dominant mechanism of Cr(VI) removal. HBC, nZVI-HBC, and Fe 3+ -HBC were more effective for Cr(VI) removal than was BC. Fe 3+ in Fe 3+ -HBC was reduced to Fe 2+ by HBC; thus, Cr(VI) was reduced by Fe 2+ . The amount of Cr(III) released into aqueous solution depended on the adsorbent types. Abstract: Willow residue biochar (BC) and modified biochars (hydrochloric acid washing (HBC), HBC loaded with nanoscale zero-valent iron (nZVI-HBC), and HBC loaded with ferric iron (Fe 3+ -HBC)) after aging were used for aqueous Cr(VI) removal. HBC (>98.67%), nZVI-HBC (>98.86%), and Fe 3+ -HBC (>99.64%) kept high Cr(VI) removal rates under the acidic conditions within a wide pH range (<7.0), indicating their good adaptability to pH change because of aging. Cr(VI) reduction to Cr(III) was the dominant removal mechanism. The formation of COOH on BC, HBC, and nZVI-HBC indicates the oxidation of surface functional groups by Cr(VI) and simultaneous Cr(VI) reduction. The disappearance of nZVI peaks indicates the reduction of Cr(VI) to Cr(III) by nZVI. The color reaction result demonstrated that the converted Fe 2+ in Fe 3+ -HBC contributed to Cr(VI) reduction. Taking into account the removal efficiency, recyclability, cost, preparation process, and stability of adsorbents, Fe 3+ -HBC was recommended for Cr(VI) removal.